Discussion of “Were Information Intermediaries Sensitive to the Financial Statement‐Based Leading Indicators of Bank Distress Prior to the Financial Crisis?” - Ryan, Stephen G. (Contemporary Accounting Research, 2016)
Abstract I discuss Desai, Rajgopal, and Yu ( ) with the goal of helping readers think carefully about which implications of the study are likely to generalize to future economic downturns and which are likely to be specific to the facts and circumstances of the recent financial crisis, given that the crisis was driven by the expectation and then the realization of a single market variable, national house price depreciation.